Presiding Judge Mario Olmos Keynotes Fresno County Bar Association Luncheon re Court Filings - Watkins, Howard::::::::: (1989)
Fresno County Bar Association President-Elect bb introducing Fresno Superior Court Presiding Judge Mario Olmos